Occupational stress, psychological strain and coping resources among nurses at Institut Perubatan dan Pergigian Termaju / Noraini Hashim ... [et al.] - Hashim, Noraini; Ismail, Asiah; Tamchik, Jariah; Ibrahim, Sarimah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Increasing in workloads can be a source of stress for many nurses around the world because of the demands for higher performance and the ability to perform multi-tasking jobs. The aims of this study were to identify occupation stress, psychological strain and coping resources among the nurses in Institut Perubatan dan Pergigian Termaju (IPPT), Universiti Sains Malaysia. A cross-sectional study of 100 nurses was conducted in various departments at IPPT. Validated questionnaire Occupational Stress Inventory – Revised (OSI-R) was used in data collection. Senior staff aged 41-50 years old perceived higher level of stress relating role boundary and responsibility rather than the junior staff (p=0.011). The senior staffs are also perceived higher level of psychological strain compared with the junior staff. As conclusion, there is a positive correlation between age and occupational stress, psychological strain, and coping resources among IPPT nurses